Estetika Tari Gambyong Solo Minulya Karya S. Maridi - Sumargono, Sumargono (Institut Seni Indoensia Surakarta, 2009)
This writing will disclose and identify the aesthetics of Gambyong Solominulya dance by applying a special attention to the analysis of dance’s elements and the ralations of one element to the others. The notation patterns of the music dance were described in detail so that it was possible to identify the tempo, laya, rhyme, musical tate and the pattern of kendangan mungkus / mlaku. The result is that we know the choreography of Gambyong Solominulya dance has a harmonious impression. This aesthetic analysis was based on the aesthetic concept of Javanese traditional dancing of Surakarta style, both the technique and its taste. The concept covers pacak, pancat,lulut, luwes, ulat, wiled, rhyme and gendhing which are known as hastha sawanda. This writing at least can make a contribution to the aesthetic analysis on dance of Surakarta style and possibly other style.Keyword : Gambyong, aesthetic, gendhing, dance movement, dramatic design